A Designers' Perspective on Additive Manufactured Smart Wearables for Paediatric Habilitation. (May 2022) - Bonello, M.; Farrugia, P.
Abstract: The aim of the paper is to identify from the perspective of designers, what is required to optimally design smart habilitation devices for additive manufacturing, whilst ensuring a high quality multi-user experience. Semi-structured interviews were conducted with designers to identify the key requirements to develop such devices. The outcome of this study will provide a preliminary framework for designers to take advantage of the state-of-the-art of design for additive manufacturing in order to meet the expectations of multiple users of smart devices for pediatric occupational therapy.